STUDENTS’ LEARNING STYLE ANALYSIS IN ENHANCING DIFFERENTIATED INSTRUCTION AT SD NEGERI 1 ROWOHARJO - Dewi Sekar Sari; Dhea Ayu Laura; Anisa Nasywa Zhahiroh; Abu Rijal Maulana Bekti; Ferril Irham Muzaki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the variations in students' learning styles and their relationship with the implementation of differentiated instruction at SD Negeri 1 Rowoharjo. A systematic literature review (SLR) following the PRISMA protocol (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) was conducted on 11 selected articles retrieved from Google Scholar, SINTA, and nationally accredited journal portals, and was integrated with empirical field data obtained through in-depth interviews with three teachers. The findings consistently reveal that elementary school students possess heterogeneous learning styles, with a dominance of the kinesthetic modality followed by visual and auditory preferences. Teachers at SD Negeri 1 Rowoharjo have made efforts to accommodate these differences through the use of visual media, class discussions, and hands-on activities; however, such efforts remain situational and have not been grounded in systematic learning style mapping. Identification of learning styles through the VARK model proves to be a practical and relevant framework for designing adaptive instructional strategies. This study concludes that structured mapping of students' learning styles is an essential prerequisite for effective, innovative, and student-centered differentiated instruction.